2018
DOI: 10.1002/chem.201802054
|View full text |Cite
|
Sign up to set email alerts
|

Injectable Oxygen: Interfacing Materials Chemistry with Resuscitative Science

Abstract: Intravascular oxygen delivery holds great potential to treat numerous hypoxic conditions and emergencies, including pulmonary disorders, hypoxic tumors, hemorrhagic shock, stroke, cardiac arrest and so on. Tremendous effort has been made in the past to find material solutions for the development of intravenous oxygen carriers and have ranged from blood substitutes to microbubbles with limited success. This paper highlights previous and recent progress in perfluorocarbon-emulsions and microbubbles as intravenou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 92 publications
0
8
0
Order By: Relevance
“…We systematically varied the number, placement, and dimensions of both the step changes and the nozzles ( SI Appendix , Figs. S1–S4 ) and evaluated their ability to stably spray oxygen nano/microbubbles at the required volumetric flow rates [e.g., 0.05 to 0.5 mL O 2 /min or ∼1 to 10% of the baseline oxygen consumption of Sprague-Dawley rats; we have previously demonstrated that delivering ∼0.5 mL O 2 /min or 10% VO 2 was sufficient to resuscitate rats from 10 min of asphyxia leading to cardiac arrest ( 21 )]. We found that the optimal device geometry had an oversized nozzle at the two-phase junction (120 μm) followed by an immediate step change in channel depth from 30 μm to 55 μm ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We systematically varied the number, placement, and dimensions of both the step changes and the nozzles ( SI Appendix , Figs. S1–S4 ) and evaluated their ability to stably spray oxygen nano/microbubbles at the required volumetric flow rates [e.g., 0.05 to 0.5 mL O 2 /min or ∼1 to 10% of the baseline oxygen consumption of Sprague-Dawley rats; we have previously demonstrated that delivering ∼0.5 mL O 2 /min or 10% VO 2 was sufficient to resuscitate rats from 10 min of asphyxia leading to cardiac arrest ( 21 )]. We found that the optimal device geometry had an oversized nozzle at the two-phase junction (120 μm) followed by an immediate step change in channel depth from 30 μm to 55 μm ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…LOMs have also been devised to release oxygen within the bloodstream. Yet, a key limitation of using LOMs within the circulatory system is their associated risk of causing acute pulmonary vascular obstruction due to lipid shedding, resulting in the subsequent formation of large lipid aggregates [100]. Recently, dextran-acetyl-succinate LOMs were adopted to address this challenge.…”
Section: Trends In Biotechnologymentioning
confidence: 99%
“…Owing to the ability to carry oxygen, PFC-loaded NPs find application in photodynamic 1 4 and other hypoxia-affected treatments of cancer 5 , 6 and treatment of stroke. 7 , 8 Additionally, they act as multimodal imaging agents for 19 F magnetic resonance imaging ( 19 F MRI) and ultrasound. 9 12 PFCs, however, have already seen a long and much more varied history of clinical use.…”
Section: Introductionmentioning
confidence: 99%
“…Perfluorocarbon (PFC)-loaded nanoparticles (NPs) emerged recently as powerful theranostic agents that could lead to the treatment of major public health problems. Owing to the ability to carry oxygen, PFC-loaded NPs find application in photodynamic and other hypoxia-affected treatments of cancer , and treatment of stroke. , Additionally, they act as multimodal imaging agents for 19 F magnetic resonance imaging ( 19 F MRI) and ultrasound. PFCs, however, have already seen a long and much more varied history of clinical use. They were first used in the 1980s as blood substitutes because of their ability to dissolve oxygen.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation